Large CO2 release and tidal flushing in salt marsh crab burrows reduce the potential for blue carbon sequestration. Issue 1 (4th September 2020) - Xiao, Kai; Wilson, Alicia M.; Li, Hailong; Santos, Isaac R.; Tamborski, Joseph; Smith, Erik; Lang, Susan Q.; Zheng, Chunmiao; Luo, Xin; Lu, Meiqing; Correa, Rogger E.
Abstract: Abundant crab burrows in carbon‐rich, muddy salt marsh soils act as preferential water flow conduits, potentially enhancing carbon transport across the soil–water interface. With increasing recognition of blue carbon systems (salt marshes, mangroves, and seagrass) as hotspots of soil carbon sequestration, it is important to understand drivers of soil carbon cycling and fluxes. We conducted field observations and flow modeling to assess how crab burrows drive carbon exchange over time scales of minutes to weeks in an intertidal marsh in South Carolina. Results showed that continuous advective porewater exchange between the crab burrows and the surrounding soil matrix occurs because of tidally driven hydraulic gradients. The concentrations of dissolved inorganic (DIC) and organic (DOC) carbon in crab burrow porewater differ with that in the surrounding soil matrix, implying a diffusive C flux in the low‐permeability marsh soil. Gas‐phase concentrations of CO2 in ∼ 300 crab burrows were approximately six times greater than ambient air. The estimated total C export rate via porewater exchange (1.0 ± 0.7 g C m −2 d −1 ) was much greater than via passive diffusion transport (6.7 ± 2 mg C m −2 d −1 ) and gas‐phase CO2 release (0.93 mg C m −2 d −1 ). The burrow‐related carbon export was comparable to the regional salt marsh DIC export, groundwater‐derived DIC export, and the net primary production previously estimated using ecosystem‐scale approaches. These insights reveal how crab burrows modify blue carbon sequestration in salt marshes and contribute to coastal carbon budgets.